Heavy metals in the soil of copper pyrities vicinities fields «Molodeznyi» (Chelyabinsk region) (Eurasian Journal of Ecology, 2016)
The heavy elements (Cu, Zn, Ni, Mn, Fe, Cd, Pb) cotent in soils of copper pyrities vicinities fields is defined. Authors revealed mosaicity of their contents depending on distance from a pit. The sites having excess of maximum concentration limit on the content of copper, zinc and nickel are established.
Keywords: heavy elements; soil; pyrities vicinities fields; zinc; nickel; maximum concentration limit